A review on piezoelectric energy for smart street and traffic lights. Issue 1 (2nd January 2022) - Hans, Drishti; Gandhar, Shashi; Aggarwal, Ayush; Batra, Ishita; Singh, Kartick H
Abstract: There's a need to look for alternate sources of energy due to increasing population. The utilization of energy from the vibrations created by the vehicles and the activity by people is relevant for the energy deficient countries. This review incorporates various research papers that deal with piezoelectric materials to generate energy. Along with different techniques to increase energy efficiency, papers dealing with integration of piezoelectric sensors with smart street and traffic lights have also been reviewed. However, the authors believe that with further research into piezoelectric material, a model can be proposed which is both time and energy efficient.